Activity of essential oils and hydroalcoholic extracts from 12 plants against food spoilage yeasts: evaluation of their potential as new biopesticides - Pereira, Bruna Daniela Fernandes (2021)
Dissertação de mestrado em Biologia Molecular, Biotecnologia e Bioempreendedorismo em Plantas